PENGARUH MENGAKSES GAME ONLINE MOBILE LEGENDS TERHADAP PERILAKU KOMUNIKASI DALAM BERSOSIALISASI REMAJA DI KOTA BATAM - Dayanti, Dayanti; Syafi'i, Muhammad (LPPM Universitas Putera Batam, 2020)
Based on preliminary observations made by researchers showed that many teenagers who access mobile legends online games and online games have a significant influence on communication behavior. The purpose of this study was to determine the effect of accessing online legends mobile games on communication behavior in socializing teenagers in Batam The method used in this study is quantitative with a simple linear regression analysis with the help of SPSS 22. The sample in this study was 100 respondents with a random sampling method. The results showed the value of t arithmetic (7.994) > t table (1.98447) with a significance of 0,000 < 0.05 which indicates online games have a significant influence on communication behavior. R square coefficient test of 0.395 shows that online game variables have an effective contribution of 39.5% of communication behavior and the remaining 60.5% of communication behavior is influenced by variables not examined in this study. Keywords: Communication Behavior, Mobile Legends, Online Games